Cross-Cultural Challenges and Self-Efficacy of Indonesian EFL Teachers In Thailand - Ainifitria Dueramae; Pirman Ginting (Jurnal Ragam Pengabdian, 2026)
This article examines the level of perceived self-efficacy and pedagogical challenges faced by pre-service Indonesian teachers of English as a Foreign Language (EFL) during their international teaching practice in Thai classrooms. Based on Bandura's self-efficacy theory and grounded in a sociocultural perspective, this study employs a qualitative case study design. Data were collected through an online questionnaire consisting of Likert scale questions and open-ended questions, and analyzed using thematic analysis supported by descriptive interpretation of response patterns. The results showed that participants generally demonstrated moderate to high levels of self-confidence in classroom management, teaching strategies, and student engagement. Despite facing challenges such as language barriers, cultural differences, and teaching adjustments, participants developed adaptive strategies that strengthened their professional self-confidence. This study concludes that self-confidence in a cross-cultural context is socially constructed through experiential learning and intercultural interactions, highlighting the importance of integrating structured international practice programs into teacher education curricula